2007
DOI: 10.1093/brain/awl338
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala dysfunction in men with the fragile X premutation

Abstract: Premutation alleles (55-200 CGG repeats) of the fragile X mental retardation 1 (FMR1) gene are associated with autism spectrum disorder in childhood, premature ovarian failure, and the neurodegenerative disorder, fragile X-associated tremor/ataxia syndrome (FXTAS). FXTAS, and perhaps the other clinical presentations among carriers, are thought to be due to toxic gain-of-function of elevated levels of the expanded-repeat FMR1 mRNA. Previous structural MRI studies have implicated the amygdala as a potential site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
118
3
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(136 citation statements)
references
References 54 publications
13
118
3
1
Order By: Relevance
“…Structural and functional imaging studies in premutation carriers support this thesis. Notable amygdala abnormalities in male carriers include an impaired response to fearful faces, a significant negative correlation of amygdala volume with CGG size for the 55-85 repeat range, and grey matter volume loss in men with FXTAS [53][54][55]. Additionally, female carriers displayed a significant negative correlation between the hippocampal volume and severity of anxiety symptoms [56].…”
Section: Neuropsychiatric Symptomsmentioning
confidence: 97%
“…Structural and functional imaging studies in premutation carriers support this thesis. Notable amygdala abnormalities in male carriers include an impaired response to fearful faces, a significant negative correlation of amygdala volume with CGG size for the 55-85 repeat range, and grey matter volume loss in men with FXTAS [53][54][55]. Additionally, female carriers displayed a significant negative correlation between the hippocampal volume and severity of anxiety symptoms [56].…”
Section: Neuropsychiatric Symptomsmentioning
confidence: 97%
“…All subjects whose data is reported here also participated in a study of amygdala function whose results are reported in the Hessl et al (2007) paper referenced above. The two groups did not differ in age, Full Scale IQ (117.9, 113.4; t=0.54, p=0.60), level of education and overall psychiatric symptomology as measured by the SCL-90-R Global Severity Index (see Table 1).…”
Section: Participantsmentioning
confidence: 99%
“…Recently, data from our laboratory has suggested that brain function is also affected by premutation status in relatively young premutation carriers without FXTAS who demonstrate no overt neurological symptoms. Compared with controls on an fMRI task, men with the premutation showed diminished brain activation in the amygdala and several brain areas that mediate social cognition while viewing fearful faces (Hessl et al 2007). The reduced amygdala activation in this group was also significantly associated with self-report of psychiatric symptoms on the Symptom Checklist-90-Revised (SCL-90-R).…”
Section: Introductionmentioning
confidence: 97%
“…For example, psychological symptoms, such as anxiety and obsessive-compulsive features are associated with abnormal elevation of FMR1 mRNA in adult male premutation carriers with and without FXTAS (15). Also, both reduced FMRP and elevated mRNA contribute to alterations in limbic function and symptom expression in young adult carriers (30,31), providing a gene-brain-behavior basis for an understanding of emergence of these difficulties.…”
Section: Introductionmentioning
confidence: 99%